2010
DOI: 10.1038/jp.2010.95
|View full text |Cite
|
Sign up to set email alerts
|

Association of cord blood platelet count and volume with hemoglobin in healthy term infants

Abstract: Objective: The aim of this study was to investigate relationships of cord blood cells in healthy term infants both from vaginal and Cesarean sections.Study Design: The study sample comprised 167 consecutive cord blood collections accepted for processing in an accredited cord blood bank. The effect of varying anticoagulant-to-blood ratio was excluded by standardizing the cell concentrations to reflect the values in native blood. Statistical analysis included descriptive statistics, simple linear regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
5
4
0
Order By: Relevance
“…We analyzed a pretty much larger number of CB units in our study (10,577); therefore, we believe there is no proof of relationship between MPV and platelet concentration. Our finding that MPV positively correlated with Hb is consistent with that of a previous study [6]. MPV was also positively correlated with WBC concentration.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We analyzed a pretty much larger number of CB units in our study (10,577); therefore, we believe there is no proof of relationship between MPV and platelet concentration. Our finding that MPV positively correlated with Hb is consistent with that of a previous study [6]. MPV was also positively correlated with WBC concentration.…”
Section: Resultssupporting
confidence: 93%
“…The present study shows that the MPV of CB correlates with TNC and CD34+ cell counts and the ratio of CD34+ cells to TNCs in the processed CB units, which is consistent with the results of previous studies [4, 6]. Our study is significant because of the large number of CB units analyzed from a Korean CB bank.…”
Section: Resultssupporting
confidence: 92%
“…In the current study, the total WBC , neutrophil and monocyte differential count of neonates delivered by NVD were significantly higher than those delivered by ECS (Table 2) and ( Table 3). These results were in agreement with that of Al-Mudallal and Al-Habbobi, Redźko S, et al , Eskola et al, Lee et al, El Gendy et al and Chirico, et al 8,17,23,20,25,30 . This is because during labor there is a combination of severe stress and physical stimulus, to the mother and periodic physical stress resulting from intermittent episodes of hypoxia during labor, to the featus.…”
Section: Discussionsupporting
confidence: 90%
“…his study showed that there were no statistically significant differences in the hemoglobin and hematocrit values between normal vaginal delivery (NVD), elective cesarean section (ECS) (Table 1). These results were similar to that observed by Al- 19,20,21,22,23,13,24,25,26 .Their studies reported significally increased levels of Hb and Hct in vaginally born infants compared with infants born by caesarean section. The differences in the results may be due to the sample size, environmental and, time of cord blood collection, site of collection of cord blood, physiological conditions of mode of delivery, the state of physical activity of the baby and their studies conducted on preterm newborns and with abnormal birth weights.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation